2007
DOI: 10.1111/j.1365-2494.2007.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of livestock breed and grazing intensity on biodiversity and production in grazing systems. 2. Diet selection

Abstract: Summary Reduction in grazing intensity and the use of traditional instead of commercial breeds have frequently been recommended to meet biodiversity and production goals in sustainable grazing systems. The impact of such practices within a range of contrasting grassland vegetation types was studied. This paper describes the effects on foraging behaviour in a study conducted over three years on mesotrophic or semi‐natural grasslands in UK (steers), Germany (steers), France (heifers) and Italy (sheep). Three tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 44 publications
8
76
1
1
Order By: Relevance
“…Ewes have also been observed to select short areas from the end of spring and continue to avoid tall areas at the end of the grazing season in a cocksfoot plot grazed at a low stocking rate (Garcia et al, 2004). In a direct comparison that took place in four mesotrophic or semi-natural grasslands across western Europe, Dumont et al (2007) reported that cattle and sheep showed more-pronounced selection of wellgrazed areas of better quality in productive mesotrophic vegetations than in semi-natural grasslands with a strong fine-scale heterogeneity and a relatively high nutritive value. However, the authors hypothesised that a more pronounced patch grazing response could occur in semi-natural grasslands if they were grazed at a lower stocking rate, which is confirmed by our observation that heifers grazing at the lowest stocking rate tended to better maintain their selection for short patches at the end of the season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ewes have also been observed to select short areas from the end of spring and continue to avoid tall areas at the end of the grazing season in a cocksfoot plot grazed at a low stocking rate (Garcia et al, 2004). In a direct comparison that took place in four mesotrophic or semi-natural grasslands across western Europe, Dumont et al (2007) reported that cattle and sheep showed more-pronounced selection of wellgrazed areas of better quality in productive mesotrophic vegetations than in semi-natural grasslands with a strong fine-scale heterogeneity and a relatively high nutritive value. However, the authors hypothesised that a more pronounced patch grazing response could occur in semi-natural grasslands if they were grazed at a lower stocking rate, which is confirmed by our observation that heifers grazing at the lowest stocking rate tended to better maintain their selection for short patches at the end of the season.…”
Section: Discussionmentioning
confidence: 99%
“…We have observed that under a medium stocking rate, cattle grazing species-rich mountain pasture exploited short patches of better quality less intensively than those grazing in mesotrophic swards characterised by low-to-moderate plant species diversity (Dumont et al, 2007). It was however hypothesised that there would be a stronger patch grazing response (as described by Adler et al, 2001) in species-rich pastures if they were grazed at a very low stocking rate.…”
Section: Introductionmentioning
confidence: 96%
“…However, in their review, Rook et al (2004) found little evidence of breed differences in grazing preferences. Likewise, Fraser et al (2009) recorded no differences in the impact of grazing by native and continental cross steers while Dumont et al (2007) found few differences in the diet choices made by commercial and traditional breeds of cattle. Table 2 presents results from a study by McCloskey et al (2009a) in which Blackface and Swaledale, Cheviot, Lleyn and Texel cross Blackface ewes grazed six different hill areas in Northern Ireland.…”
Section: Impact Of Grazing On Biodiversity and Environmental Charactementioning
confidence: 93%
“…They include especially: characterizing each paddock by its function in the feeding system (Fleury et al, 1996), applying Jouven, Lapeyronie, Moulin and Bocquier moderate stocking densities (Dumont et al, 2007) and adjusting the residual sward height to overall forage availability on farm scale (Duru et al, 2002).…”
Section: Indicators To Support Grazing Management Decisions In Heteromentioning
confidence: 99%